Effects of Adhesive Connection on Composite Action between FRP Bridge Deck and Steel Girder - Xu Jiang; Chengwei Luo; Xuhong Qiang; Henk Kolstein; Frans Bijlaard (Journal of Engineering)
The FRP-steel girder composite bridge system is increasingly used in new constructions of bridges as well as rehabilitation of old bridges. However, the understanding of composite action between FRP decks and steel girders is limited and needs to be systematically investigated. In this paper, depending on the experimental investigations of FRP to steel girder system, the Finite Element (FE) models on experiments were developed and analyzed. Comparison between experiments and FE results indicated that the FE models were much stiffer for in-plane shear stiffness of the FRP deck panel. To modify the FE models, rotational spring elements were added between webs and flanges of FRP decks, to simulate the semirigid connections. Numerical analyses were also conducted on four-point bending experiments of FRP-steel composite girders. Good agreement between experimental results and FE analysis was achieved by comparing the load-deflection curves at midspan and contribution of composite action from FRP decks. With the validated FE models, the parametric studies were conducted on adhesively bonded connection between FRP decks and steel girders, which indicated that the loading transfer capacity of adhesive connection was not simply dependent on the shear modulus or thickness of adhesive layer but dominated by the in-plane shear stiffness K.